Feed and nutrition research for development and feed technology entry point in the smallholder poultry systems - Essien, E.; Goromela, E.H.; Olukosi, A.O.; Sonaiya, Emmanuel B.; Dessie, Tadelle (2019)
Smallholder poultry (SHP) are kept in scavenging, small scale, free-range and backyard systems which depend for feed and nutrition on the scavengeable feed resource base (SFRB). The quantity and quality of SFRB varies with season, altitude, climatic conditions, farming activities and village flock biomass but SFRB may contain low concentration of protein, energy and minerals indicating the need for supplementary feeds. Research for development (R4D) approaches have focused on quantitative assessment and nutrient evaluation of SFRB; strategies to optimize the use of SFRB by smallholder poultry production systems in Africa; evaluation of alternative ingredients that are less competitive with humans but abundantly available in local areas or regions for adoption by market driven community feed resource centers; farmers perceptions on the use of non-conventional animal protein sources for scavenging chickens (e.g. insects and worms); effects of alternative ingredients for supplementary feed on growth, carcass yield and egg production in order to answer the growing need of more productive chicken breeds that are increasingly coming into the SHP system. Novel technologies such as accurate prediction and determination of digestible phosphorus and digestible calcium must be carefully introduced into the scavenging system in order to produce greater benefits than costs.